PENGARUH RASIO PROFITABILITAS, RASIO SOLVABILITAS DAN RASIO NILAI PASAR TERHADAP RETURN SAHAM PERUSAHAAN REAL ESTATE DAN PROPERTI - Nestanti, Desy Dwi (Department of Management, 2017)
The purpose of this study was to analyze the influence of financial ratios, as measured by the ratio of profitability, solvability ratio and the ratio of the market value of the stock returns of real estate companies and property and to determine which variables are the most significant effect on stock returns. The analysis tool used is multiple linear equations with multiple regresion method for the analysis of the influence of the independent variable on the dependent variable. This model was chosen because the study was designed to determine the independent variables that have an influence on the dependent variable. The result of F test (simultaneous) shows that the financial ratios of return on equity and price to book value have a significant effect on stock returns and partial results showed that the variable return on equity have a significant effect on the analysis tehadap return saham. Berdasarkan diterdapat variables have a significant influence on stock returns. The variable that has no significant effect on stock returns are removed from the multiple linear regression equation. So the result shows that the return on equity and price to book value have a significant effect on stock returns.